STRATEGI WIRAUSAHAWAN UMKM DAN PELUANG MAHASISWA BERWIRAUSAHA - Tedy Ardiansyah (Fakultas Ekonomi Universitas Negeri Jakarta, 2017)
This study aims to determine the relationship strategy entrepreneur umkm against entrepreneurship student opportunities. The study was conducted at two (2) universities in Jakarta. This research uses survey method with descriptive and associative approach. Data were collected by using questionnaires distributed to 64 respondents. The data were analyzed by using validity and reliability test, while the test of variable by using regression and correlation test. The results show that 1) entrepreneurial strategy has a significant impact on the opportunity of entrepreneurial students 2) although in two (2) different universities both the number of respondents and gender, but the results show the same results Keywords: Entrepreneur, Entrepreneurship, UMKM, Student